Effect of growth hormone cotreatment in subfertile women ≥ 40 years: a meta-analysis - Mohamed Elkalyoubi; Larissa Schindler; Hena Zaheer (Bioscientifica, 2023)
Treatment of sub-fertile women aged ≥ 40 years old (advanced maternal age (AMA)) is challenging. Co-treatment with growth hormone (GH) is suggested to improve reproductive outcomes in poor responders. However, few studies, and with conflicting results, focused on women of AMA. A systematic review and meta-analysis of randomized controlled trials (RCTs) and comparative retrospective trials (CRTs) of GH cotreatment in AMA women undergoing in vitro fertilization or intracytoplasmic injection treatment using their autologous oocytes was performed. The search included studies published in English up to the end of 2021. The primary outcome was the clinical pregnancy rate per embryo transfer. Secondary outcomes were the number of mature and retrieved oocytes and the rate of live birth. A total of 406 studies were found. The final analysis included 3 RCTs and 4 CRTs with 481 patients who used GH and 400 patients who did not. Clinical pregnancy and live birth rates were significantly higher in the GH cotreatment group compared to the placebo as well as the group without GH co-treatment, (odds ratio (OR): 2.2; 95% CI: 1.34-3.61 and OR: 4.12; 95% CI: 1.82-9.32, respectively). Intriguingly, the subgroup analysis showed that poor-responder patients did not benefit from co-treatment with GH. There were no statistically significant differences in the number of mature or retrieved oocytes. GH cotreatment in a subgroup of women of AMA improves clinical pregnancy and live birth per fresh embryo transfer. However, this conclusion must be taken with caution and further research is needed. The review is registered in the PROSPERO database (www.crd.york.ac.uk/prospero/; CRD42021252618).